Capillary haemangioma of the ethmoid sinus. (10th April 2013) - Lightbody, Kathryn A; Wilkie, Mark D; Luff, David A
Abstract : A middle-aged male presented with unilateral nasal blockage, reduced sense of smell and daily nosebleeds. He had a history of nasal polyps, and had undergone a left-sided polypectomy and ethmoidectomy some 10 years previously. A large polpypoid mass was visible within the right nasal cavity upon examination, with CT and MRI imaging confirming the presence of a large soft tissue abnormality with no intracranial extension. Following biopsy suggestive of angioma, the patient underwent embolisation of the mass prior to endoscopic resection. Subsequent pathology revealed the mass to be a capillary haemangioma. The man made good postoperative progress and was asymptomatic at early follow-up.